Ebargofiant - Hunter, Jerry (Y Lolfa, 2014)
A novel set in the future following a social and ecological upheaval where people live in a primitive way in a barren world. Life is tough and short in a society where hardly anyone is able to write, and the autobiography of the main character follows his quest for literacy. Intro – 1 – 2 – 3 – 4 – 5 – 6 – 7 – 8 – 9 – 10 – 1dros10 – 2dros10 – 3dros10 – 4dros10 – 5dros10 – 6dros10 – 7dros10 – 8dros10 – 9dros10 – 10a10to – 1dros10a10to – 2dros10a10to – 3dros10a10to – 4dros10a10to – 5dros10a10to – 6dros10a10to.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books